Urgensi Akta Lahir Dalam Persyaratan Pencatatan Perkawinan Perspektif Maqashid Syariah - Daffa Zaidani Annafiq (SAKINAH: Jurnal Hukum Keluarga Islam, 2023)
Abstract: This research aims to examine the urgency of a birth certificate as a condition for marriage. and maqashid sharia's views on PMA No. 20 of 2019 Article 4 Paragraph 1 Letter B. This research is classified as a type of library research that is juridical-normative in nature. And has two approaches, namely; first, the Legislative Approach (statue approach). Second, the Conceptual Approach. The conclusions from this research are: 1.) Birth certificate as a requirement for marriage applications at the KUA office as formulated in article 4 paragraph 1 letter b PMA No. 20 of 2019 is very urgent in terms of its position based on the laws and regulations regarding marriage to support the fulfillment of the harmony and requirements of marriage in the aspect of the origin of the prospective bride and groom and the determination of the marriage guardian for the prospective bride. And if the birth certificate attached is indicated to be a fake birth certificate or there is manipulation in the document, then the registration status of the marriage will at the KUA can be suspended or cancelled. 2.) Maqashid sharia's view of the provisions of article 4 paragraph 1 letter b PMA No. 20/2019 concerning the attachment of a photocopy of a birth certificate as a condition for applying for marriage is a secondary requirement (hajiyyat) to perfect the marriage law which has a dharuri position. And marriage is a sharia whose status a quo has been determined based on the Al-Qur'an and Hadith, so that the implementation of marriage is an implementation of the principle of hifz ad-din (maintaining religion). As well as attaching a photocopy of a person's birth certificate or letter of origin from an authorized official as contained in article 4 paragraph 1 letter b is not only valuable as an administrative requirement, but is also valuable for implementing the principles of maqashid sharia, namely hifz an-nasl (protecting descendants/nasab ). Keywords: Kafa'ah, Modern Era, Maqashid Syariah. Abstrak: Penelitian ini memiliki tujuan untuk mengkaji urgensi akta lahir sebagai syarat perkawinan. dan pandangan Maqashid Syariah terhadap PMA No. 20 Tahun 2019 Pasal 4 Ayat 1 Huruf B. Penelitian ini terklasifikasi dalam jenis penelitian kepustakaan yang bersifat yuridis-normatif. Dan memiliki dua pendekatan yaitu; pertama, Pendekatan Perundang-undangan (statue approach). Kedua, Pendekatan Konseptual (conseptual approach). Kesimpulan dari penelitian ini adalah: 1.) Akta kelahiran sebagai persyaratan pengajuan perkawinan di kantor KUA yang dirumuskan dalam Pasal 4 ayat 1 huruf b PMA No. 20 tahun 2019 sangatlah urgen dalam segi kedudukannya berdasarkan peraturan perundang-undangan tentang perkawinan untuk menunjang terpenuhinya rukun dan syarat perkawinan dalam aspek asal usul calon pengantin dan penentuan wali nikah bagi calon pengantin perempuan. Dan jika akta kelahiran yang dilampirkan terindikasi merupakan akta kelahiran palsu atau terdapat manipulasi dalam dokumennya, maka status pendaftaran kehendak perkawinan di KUA dapat ditangguhkan atau dibatalkan. 2.) Pandangan Maqashid Syariah terhadap ketentuan Pasal 4 ayat 1 huruf b PMA No. 20/2019 tentang melampirkan foto copy akta kelahiran sebagai syarat pengajuan perkawinan adalah berkedudukan sebagai kebutuhan sekunder (hajiyyat) untuk menyempurnakan syariat perkawinan yang memiliki kedudukan dharuri. Dan perkawinan merupakan syariat yang status a quo telah ditetapkan berdasarkan AlQur’an dan Hadist, sehingga pelaksanaan perkawinan merupakan implementasi dari prinsip hifz ad-din (memelihara agama). Serta melampirkan foto copy akta kelahiran atau surat asal usul seseorang dari pejabat berwenang yang terdapat dalam Pasal 4 ayat 1 huruf b tidak hanya bernilai sebagai persyaratan administratif, akan tetapi juga bernilai untuk mengimplementasikan prinsip dari Maqashid Syariah yaitu hifz an-nasl (menjaga keturunan/nasab). Kata Kunci: Kafa’ah, Era Modern, Maqashid Syariah.